2017
DOI: 10.1016/j.ipm.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A visual UML-based conceptual model of information-seeking by computer science researchers

Abstract: abst r a ctThe information-seeking process carried out by researchers is complex and full of differ-ent variables. We have represented this complexity for computer science researchers in the form of a conceptual model. The model is presented in a visual form using the UML mod-eling language, since it allows conveying all the complexity present in such a process with greater clarity. It has been obtained after carrying out two qualitative studies -a focus group and semi-structured interviews-with computer scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The starting point for this work is the result of a qualitative study performed by Moral et al [52] to analyse the information-seeking process performed in the computer science research context. The result of this qualitative study was a coding system including 169 codes that were used to code the answers of the 17 researchers that were interviewed or participated in a focus group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The starting point for this work is the result of a qualitative study performed by Moral et al [52] to analyse the information-seeking process performed in the computer science research context. The result of this qualitative study was a coding system including 169 codes that were used to code the answers of the 17 researchers that were interviewed or participated in a focus group.…”
Section: Methodsmentioning
confidence: 99%
“…The main characteristic of information visualization, regardless of its purpose, is to "use [...] computer-supported, interactive, visual representations of abstract data to amplify cognition" [19]. Moral et al [52] conducted a qualitative study of the information-seeking processes performed by computer science researchers and then concluded that information visualization is essential to help researchers analysing hundreds or thousands of documents in order to find those that fulfil their information needs [51]. This is due to the inner perception and cognitive capacities of humans to recognize, process, and analyse visual representation that allow inferring complex information and resolving logical problems [10,86].…”
Section: Introductionmentioning
confidence: 99%
“…The main focus was placed on classic models of information seeking (Ellis, ; Kuhlthau, ; Marchionini, ; Wilson, ) because they provided original and most specific characterizations of the above issues. It appeared that even though more recent models (e.g., Foster, ; Joseph et al, ; Moral et al, , Wilson, ) insightfully make use of the ideas presented in the classic frameworks, these studies do not add much new to the picture of information‐seeking processes as temporal developments.…”
Section: Methodsmentioning
confidence: 99%
“…These models have tended to focus on information seeking behaviour and the information seeker rather than looking at the role of information in the process of making a decision. The sequential linear models have been critiqued by LIS scholars who have developed models which represent the information seeking process as a cyclical and iterative process [36,[47][48][49][50][51][52][53][54][55][56].…”
Section: Information Behaviour Modelsmentioning
confidence: 99%